2000
DOI: 10.1038/sj.onc.1203289
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer cells that coexpress endogenous Rb and p16 are insensitive to overexpression of functional p16 protein

Abstract: Defects of the`Rb/cyclin D1/p16 pathway' have been shown to play a critical role in the development of virtually all human malignancies assessed. To determine the contribution of G1 phase cell cycle defects to ovarian tumorigenesis, we have examined a panel of normal and tumor ovarian tissues and ovarian cancer cell lines for the expression of Rb, p16 and cyclin D1 proteins. Unlike most types of human cancer whose development involves the loss of either Rb or p16 expression, we observed the coexpression of Rb,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
(52 reference statements)
4
28
0
Order By: Relevance
“…They also observed that p16 expression induced transcriptional downregulation of the RB gene (19). Ovarian cancer cell lines coexpressing p16 and RB are insensitive to p16 overexpression, suggesting that tumors that express both genes may be unresponsive to p16 gene therapy (21). Loss of expression of the p16 tumor suppressor occurs more often in ovarian cancers lacking p53 mutations (22), consistent with the paradigm that inactivation of p53 is less important in ovarian carcinogenesis when another G 1 regulatory gene has already been inactivated.…”
Section: G 1 Regulatorssupporting
confidence: 63%
See 1 more Smart Citation
“…They also observed that p16 expression induced transcriptional downregulation of the RB gene (19). Ovarian cancer cell lines coexpressing p16 and RB are insensitive to p16 overexpression, suggesting that tumors that express both genes may be unresponsive to p16 gene therapy (21). Loss of expression of the p16 tumor suppressor occurs more often in ovarian cancers lacking p53 mutations (22), consistent with the paradigm that inactivation of p53 is less important in ovarian carcinogenesis when another G 1 regulatory gene has already been inactivated.…”
Section: G 1 Regulatorssupporting
confidence: 63%
“…These findings are in accordance with the knowledge that RB and p16 tumor suppressor genes function in the same pathway of cell cycle control. Investigations regarding the pRb/ cyclin D1/p16 pathway showed that coexpression of pRb, p16, and cyclin D1 is present in 82% of ovarian cancer tissues and cell lines, suggesting that defects in the pRb/cyclin D1/p16 pathway, other than the loss of pRb or p16, may play a major role in the development of ovarian cancer (21). Nieman et al (44) showed that for most ovarian carcinomas, RB alteration is not necessary for the development of a malignant phenotype, and RB mutation, when it does occur, may represent a sporadic event in ovarian carcinogenesis.…”
Section: G 1 -S Regulatorsmentioning
confidence: 99%
“…As mentioned earlier, we previously reported the insensitivity of RB + /p16 + ovarian cancer cell lines to adenoviralmediated overexpression of p16 protein (7). The inability of p16 to induce a G1 arrest in one of the cell lines, NIH-OVCAR-3, was associated with the persistence of RB phosphorylation, suggesting deregulation of G1 cyclin-associated kinase activity in these cells.…”
Section: Introductionmentioning
confidence: 96%
“…1). Indeed, we have previously shown that 82% of ovarian tumors and cell lines retain the expression of both RB and p16 proteins with the majority overexpressing p16 protein (7). Despite the presence of these two negative regulators of G1-phase, however, RB + /p16 + ovarian cancer cell lines are defective with regard to G1/S regulation as indicated by their insensitivity to the growth suppressive effects of ectopically overexpressed functional p16 protein (7).…”
Section: Introductionmentioning
confidence: 99%
“…37 Although the status of p16Ink4 in COLO 357 has not been described, nearly all pancreatic adenocarcinomas that have been tested lack normal p16 expression. 38 The SK -OV3 (Rb positive, p16 null ) 39 ovarian carcinoma cell line, the SAOS -2 (Rb negative) 40 and U2OS (Rb positive, low p16 ) 41 osteosarcoma cell lines, the MDA -MB -453 (Rb positive, 42 cyclin D1 amplification 43 ) breast carcinoma cell line, the WI38 normal human fibroblast cell line, and the 293 cell line were obtained from American Type Culture Collection. All of the cell lines express p84N5 detectable by Western blot analysis ( data not shown), although the relative level of expression varies by as much as 5 -fold from high -expressing lines (U2OS) to lowexpressing lines (WI38 ).…”
Section: Cell Culture and Animal Modelsmentioning
confidence: 99%